Makna Iklan ‘Ingat Pesan Ibu’ Terhadap Masyarakat di Era Pandemi (Studi Kasus Iklan “Ingat Pesan Ibu“ Khususnya pada Masyarakat Pendatang) - Muhammad Alvian Cahya (LPPM Stikosa - AWS, 2022)
Public service advertisements are media whose job is to build public trust and contain social messages. The achievement of effective public service advertisements is influenced by audience factors, the quality factor of public service advertisements, and the delivery of public service advertisements. Public trust is one of the factors increasing public participation in development which is the task of public service announcements. The purpose of this paper is to analyze the form of delivery and factors of effectiveness of public service advertisements, and to analyze the effect of public service announcements on public participation in the success of the health protocol campaign. This literature study summarizes the results of research on the effectiveness of public service advertisements, the form of delivery of public service announcements, and community participation in development. This study focuses on discussing the Public Service Advertisements (ILM) of the Ministry of Health of the Republic of Indonesia regarding COVID-19. Keywords: Public Service Advertisements, COVID-19, Community Behavior